Answer: 60, but I got other answers to but 60 was my first.
sorry if wrong.
Step-by-step explanation:
Wrong person I pay someone to do my math for me :)
Answer:
y = 0
Step-by-step explanation:
Answer:
-5n - 4
Step-by-step explanation:
The goal is to simplify this expression.
1. Distribute
-2.5 * 1 = -2.5
-2.5 * 2n = -5n
Now, we have
-2.5 - 5n - 1.5
2. Combine like terms
-2.5 + (-1.5) = -4 (+ * - = - The - cancels out the +)
3. Put it together
-5n - 4
I hope I helped!
Let me know if you need anything else!
~ Zoe
Answer:
3n^2+-3
Step-by-step explanation:
nxn +nx(-1) +3xn+ 3x(-1)